1999
DOI: 10.1084/jem.190.10.1541
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Interleukin 1 Receptor–Related T1/St2 Does Not Affect T Helper Cell Type 2 Development and Its Effector Function

Abstract: T1/ST2, an orphan receptor with homology with the interleukin (IL)-1 receptor family, is expressed constitutively and stably on the surface of T helper type 2 (Th2) cells, but not on Th1 cells. T1/ST2 is also expressed on mast cells, which are critical for Th2-mediated effector responses. To evaluate whether T1/ST2 is required for Th2 responses and mast cell function, we have generated T1/ST2-deficient (T1/ST2−/−) mice and examined the roles of T1/ST2. Naive CD4+ T cells isolated from T1/ST2−/− mice developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
142
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 42 publications
10
142
6
Order By: Relevance
“…This observation contrasts with those of Kurowska et al which showed that absence of IL-33 signalling does not affect IL-4 production [5,38]. This discrepancy can be explained by the difference in the asthma protocols or the doses of antigen administered during immunization [38][39][40]. Our model, using two sensitizations with low dose of OVA (10 mg/mouse) without adjuvant, followed by three OVA challenges (10 mg/mouse), seems to favour the development of classical Th2 cells that produce IL-4, IL-5 and IL-13, since we showed a reduction of all these cytokines in ST2-deficient mice.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This observation contrasts with those of Kurowska et al which showed that absence of IL-33 signalling does not affect IL-4 production [5,38]. This discrepancy can be explained by the difference in the asthma protocols or the doses of antigen administered during immunization [38][39][40]. Our model, using two sensitizations with low dose of OVA (10 mg/mouse) without adjuvant, followed by three OVA challenges (10 mg/mouse), seems to favour the development of classical Th2 cells that produce IL-4, IL-5 and IL-13, since we showed a reduction of all these cytokines in ST2-deficient mice.…”
Section: Discussioncontrasting
confidence: 86%
“…Interestingly, we observed that cells from mLNs of ST2-deficient mice produced less Th2 cytokines, IL-4, IL-5 and IL-13 after antigen in vitro restimulation than cells isolated from WT mice. This observation contrasts with those of Kurowska et al which showed that absence of IL-33 signalling does not affect IL-4 production [5,38]. This discrepancy can be explained by the difference in the asthma protocols or the doses of antigen administered during immunization [38][39][40].…”
contrasting
confidence: 57%
“…These results are of particular significance as studies utilising T1/ST2 À/À mice have thus far failed to demonstrate, in a number of infectious disease models, that absence of the molecule can significantly increase rates of morbidity or mortality although these reports do provide evidence of alterations in the immune response [15,16]. Consequently, given our data and a previous During T. gondii infection the parasite preferentially forms cysts in tissues of the CNS that persist for the lifetime of the host [17].…”
Section: Discussionmentioning
confidence: 99%
“…These results are of particular significance as studies utilising T1/ST2 À/À mice have thus far failed to demonstrate, in a number of infectious disease models, that absence of the molecule can significantly increase rates of morbidity or mortality although these reports do provide evidence of alterations in the immune response [15,16]. Consequently, given our data and a previous report which demonstrated particularly high levels of IL-33 expression in the brain in comparison with other organs [12], the immune modulatory role of IL-33 receptor (IL-33R) signalling may have more relevance to the brain than other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation